Multicenter Evaluation of Dynamic Three-Dimensional Magnetic Resonance Myocardial Perfusion Imaging for the Detection of Coronary Artery Disease Defined by Fractional Flow Reserve. (May 2015) - Manka, Robert; Wissmann, Lukas; Gebker, Rolf; Jogiya, Roy; Motwani, Manish; Frick, Michael; Reinartz, Sebastian; Schnackenburg, Bernhard; Niemann, Markus; Gotschy, Alexander; Kuhl, Christiane; Nagel, Eike; et al.
<x xml:space="preserve">Abstract</x> Background— First-pass myocardial perfusion cardiovascular magnetic resonance (CMR) imaging yields high diagnostic accuracy for the detection of coronary artery disease (CAD). However, standard 2D multislice CMR perfusion techniques provide only limited cardiac coverage, and hence considerable assumptions are required to assess myocardial ischemic burden. The aim of this prospective study was to assess the diagnostic performance of 3D myocardial perfusion CMR to detect functionally relevant CAD with fractional flow reserve (FFR) as a reference standard in a multicenter setting. Methods and Results— A total of 155 patients with suspected CAD listed for coronary angiography with FFR were prospectively enrolled from 5 European centers. 3D perfusion CMR was acquired on 3T MR systems from a single vendor under adenosine stress and at rest. All CMR perfusion analyses were performed in a central laboratory and blinded to all clinical data. One hundred fifty patients were successfully examined (mean age 62.9±10 years, 45 female). The prevalence of CAD defined by FFR (<0.8) was 56.7% (85 of 150 patients). The sensitivity and specificity of 3D perfusion CMR were 84.7% and 90.8% relative to the FFR reference. Comparison to quantitative coronary angiography (≥50%) yielded a prevalence of 65.3%, sensitivity and specificity of 76.5% and 94.2%, respectively. Conclusions— In this multicenter study, 3D myocardial perfusion CMR proved highly diagnostic for the detection of significant CAD as defined by FFR.